Getting the best solution from a supplier – A social capital perspective. Issue 5 (December 2020) - Jääskeläinen, Aki; Schiele, Holger; Aarikka-Stenroos, Leena
Abstract: Due to the current shift towards solution provision in many industrial markets, buyers are under increasing pressure to develop sourcing strategies to procure custom solutions for their firm in order to achieve competitive advantage. The question arises as to how buyers can ensure they get the best solutions from their suppliers and whether social capital can be applied to improve solution provision processes and value creation. Existing empirical research, however, has paid only little attention to the antecedents of suppliers' solution provision performance, i.e., their capability to diagnose buyer needs and to design and implement solutions to meet them. We tested how social capital dimensions (relational, cognitive, and structural) relate to solution provision. The study uses empirical data obtained from a survey of 475 suppliers representing both manufacturing and service industries. Partial least squares (PLS) structural equation modeling (SEM) and polynomial regression were used to analyze the data. The results demonstrate that the availability of social capital in a buyer-supplier relationship is a relevant antecedent to successful solution provision activities. However, the different dimensions of social capital are found to compensate for each other to some extent. Our study further demonstrates that solution provision is not a monolithic activity but can better be understood as a multi-phase process (diagnosis, solution design, and implementation). Different aspects of social capital may have a different impact depending on the phase of solution provision. The successful diagnosis of buyer needs mediates the effect of social capital on solution design and implementation. It is also found that production characteristics of a buyer and the type of a supplier solution affect the role of social capital in solution provision process. Highlights: This study tests how social capital supports solution provision by a supplier. PLS-SEM and polynomial regression are applied in the analysis of survey data. Social capital improves solution provision in buyer-supplier relationships. Social capital dimensions have varying effects on the activities in solution provision. Social capital is most beneficial for the diagnosis of customer needs.